Engineering and Mathematical Topics in Rainfall (IntechOpen, 2023)
The mathematics involved in describing the attributes of precipitation are embodied in the technical fields of Hydrology and Hydrometeorology. In this book, multiple experts present their work on various engineering characteristics of rainfall. The topics presented will update the readers on the recent developments and their applications across different regions of the world.